The Other Side of ﻿Garcia: The Right of Publicity and Copyright Preemption - Rothman, Jennifer E. (The Columbia Journal of Law & the Arts, 2016)
The subject of my talk is a perfect transition from the two prior talks, and a perfect place to end an entire symposium about Copyright Outside the Box—by literally getting out of the copyright box entirely, and talking about the right of publicity and its intersection with copyright law. June Besek started off this panel by describing it as being about “If authorship, what then?” and my twist on this question is, “If not authorship, what then?” Or perhaps instead the turn is toward thinking about authorship in a different way: Are we talking about the author of the underlying film or the underlying work, or instead, are we perhaps talking about a different type of authorship—meaning authorship over oneself, one’s name, or one’s likeness? This latter notion of being the author of oneself is the purview of the right of publicity. Perhaps another way of thinking about my topic is that co-panelist Jay Dougherty’s film producers should still be worried even though they ultimately won in the Ninth Circuit’s rehearing of Garcia v. Google, Inc. Or, yet another lens to consider, is to pick up where my other co-panelist, Eva Subotnik, left off— perhaps the actors and the subjects of photographs have another avenue of asserting their rights, other than copyright law. The title of this talk is “The Other Side of Garcia.” The “other side” is the right of publicity, and its interface with copyright, and in particular with the doctrine of copyright preemption. This intersection or really conflict between the two laws was actually at the heart of Garcia v. Google, although it is rarely talked about in the context of the case.